The politics of Arctic international cooperation: Introducing a dataset on stakeholder participation in Arctic Council meetings, 1998–2015. (June 2017) - Knecht, Sebastian
Contemporary Arctic transformations and their global causes and consequences have put international cooperation in the Arctic Council, the region's most important forum for addressing Arctic affairs, at the forefront of research in Northern governance. With interest in Arctic regional affairs in world politics being at a historical high, the actual participation and contribution by interested actors to regional governance arrangements, such as the Arctic Council, has remained very much a blind spot. This article introduces and analyses a novel dataset on stakeholder participation in the Arctic Council (STAPAC) for all member states, Permanent Participants and observers in Ministerial, Senior Arctic Officials' and subsidiary body meetings between 1998 and 2015. The article finds that participation in the Arctic Council varies significantly across meeting levels and type of actors, and that new admissions to the Council, a source of major contestation in recent debates, do not necessarily result in more actors attending. The article further discusses these findings in light of three prevalent debates in Arctic governance research, and shows the empirical relevance of the STAPAC dataset for the study of Arctic cooperation and conflict, observer involvement in the Arctic Council system and political representation of indigenous Permanent Participants.